The expression of TLR-2 and NOD-2 in gingival epithelium of rat after probiotic Lactobacillus reuteri supplementation to inhibit Streptococcus mutans growth - Tuti Kusumaningsih; Subijanto Marto Sudarmo; Retno Indrawati; Rini Devijanti Ridwan; Sidarningsih Sidarningsih (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2015)
Lactobacillus reuteri is probiotic from Gram positive bacteria which has specific molecular structure, consisted of peptidoglycan (PG) and lipotheihoic acid (LTA). These structure have potential in pattern recognition receptors (PRRs) activation, such as TLR-2 and NOD-2 that are the up stream of beta defensin-2 (BD-2) signaling cascade. BD-2 is antimocrobial peptides naturally produced in mouth cavity that can against Streptococcus mutans effectively. This study was aimed to prove that probiotic L. reuteri supplementation can increase the expression of TLR-2 and NOD-2 in gingival epithelium. Experimental design in this study was randomized control group post test only design. Study was carried on 24 white rat (Rattus norvegicus) Wistar strain which divided into 4 groups. Positive control was rats that induced with S. mutans, while rats in negative control group were not induced. Group I was rats that suppelemented with L. reuteri for 14 days (day 1-14) and induced with S. mutans for 7 days (day 8-14). Group II was rats that supplemented with L. reuteri and induced with S. mutans simustaneously for 14 days (day 1-14). Concentration of bacterial suspension was 108 cfu ∕ml for L. reuteri and 1010 cfu/ml for S. mutans. Both of these two bacteria was given orally to rats. TLR-2 and NOD-2 expressions were evaluated with immunohistochemistry technique. Significant differences of protein expression between each treatment groud was analyzed with ANOVA (p=0.001). TLR-2 and NOD-2 expressions were higher than negative control. It can be conclude that L. reuteri supplementation as probiotic could increase the expression of TLR-2 and NOD-2 in gingival epithelium of rat.